Effects of service-learning with one movement for a nature program on senior high school students pro-environmental behaviors - Fathul Bari; Sumarmi Sumarmi; I Komang Astina (Universitas Negeri Malang, 2022)
This study aims to determine the effect of the service-learning model using one movement for nature activities on students' pro-environmental attitudes. The design used in this study was quasi-experimental. This research was carried out at State Senior High School 1 Tanjung Bumi Madura in class XI IPS 2 as a control class and XI IPS 3 as an experimental class. Data analysis was performed using the SPSS 24.0 application. The results of the normality test suggested that the data were not normally distributed, therefore, the calculation was carried out using the Wilcoxon Signed-Rank test. Based on the results of the Wilcox-on signed-rank test, the Z value was -4.365 and the asymp sig value. (2-tailed) 0.000 was smaller than the five percent alpha level (0.05), signifying that H0 was rejected while H1 was accepted. Therefore, the service-learning model using one movement for nature activities carries effects on students' pro-environmental behavior.